Biomimetic superhydrophobic UHMWPE/nanosilica films with different sticky behavior on several metals. (4th April 2017) - Wang, Hongling; Wang, Yunxia; Sun, Chufeng; Wang, Yanbin; Su, Qiong; Wang, Jianzhang; Yan, Fengyuan
Abstract : A kind of organic–inorganic composite film with biomimetic superhydrophobic performance was prepared on several metals including steel, aluminum, and copper. The organic matrix was ultrahigh‐molecular‐weight polyethylene (UHMWPE), and the inorganic filler was nanosilica. Scanning electron microscope observation indicated addition of nanosilica greatly changed the topography of the UHMWPE film. Special convexities were formed on the surfaces of the composite films, which made the composite films rougher than that of pure UHMWPE film. The nanosilica randomly scattered on the surface of the convexities and formed hierarchical structure similar to that of some plant leaves with superhydrophobic characteristics. Interestingly, it was found that there were remarkable differences between the sliding angles (SA) of water droplet on the composite films on different metals although the contact angles (CA) of water droplet on these films were quite close. The CA on the composite films on steel was about 157°, and the SA was larger than 90°, which demonstrated obvious superhydrophobic and sticky characteristic. But to the films on aluminum and copper, the CAs on them were larger than 160° and the SAs were between 3° and 4°, which meant excellent superhydrophobic and roll‐off performance. Scanning electron microscope observation indicated that there were some micro‐orifices in the film on steel and these micro‐orifices were connected to some extent. It was believed that these micro‐orifices provided capillary force and restrained sliding of water droplet. A sticky model based on capillary mechanism was proposed. Copyright © 2017 John Wiley & Sons, Ltd.